Study of noise level status at different rice mills in Surkhet Valley, Nepal - Paudel, Dharma Raj; Baral, Hom Nath (Himalayan Physics, 2020)
Noise is an unwanted sound. High-intensity noise has a detrimental effect on the health conditions. This study aims to measure noise intensity inside different rice mills in Surkhet valley. Rice mills are spread all over Nepal from village to town. They are among the noisiest environment. Twelve mills are selected at different locations inside the valley. Noise intensities are determined by using a sound-level meter and the health conditions of the workers are concluded using a questionnaire technique. The study shows that noise level status is well above the recommended level set by the World Health Organization (WHO). It also concludes statistically that high intensity of sound causes hearing problems in workers.